POTENSI PARIWISATA DANAU SENTANI DI KABUPATEN JAYAPURA, PROVINSI PAPUA - Joice Orlince Andarita Wandikbo; Hanny Wahidin Wiranegara; Marselinus Nirwan Luru (Jurnal Lingkungan dan Kota, 2021)
Lake Sentani is a tourist destination that can be excelled in Jayapura Regency due to its location close to the Sentani international airport in Papua Province. In reality, the Lake Sentani area has not become a tourist destination for domestic and international tourists. This study aims to identify the potential elements of tourism in the Lake Sentani area that need to be developed. The method used in this study is a qualitative approach with data were carried out through field observations, collection of documentation and maps, and questionnaires. The analytical technique used is a weighting score based on the Guidelines for Assessment of Tourist Attractions of the Ministry of Culture and Tourism (ODTWA PHKA 2003) and then calculates the level of feasibility or potential using the feasibility index according to Karsudi (2010). The tourism elements analyzed include tourist attraction, supporting facilities, accessibility and community involvement. The results of the study indicate that the tourist attraction elements are feasible to be developed. There are more than 5 types of touritst attractions, including the uniqueness and beauty of natural resources. Supporting facilities deserve to be developed to support the needs of tourists. The availability of cafes/restaurants and shopping centers needs to be improved at each tourist attraction such as Khalkote Beach, Asei Island and Ayapo. Accessibility deserves to be developed, both by improving roads and providing transportation modes. The community involvement element deserves to be developed related to cleanliness issue in the Lake Sentani area